Zygomatic and Conventional Implants for Management of Severe Alveolar Atrophy in Partial Edentulous Maxilla and Completely Edentulous Mandible (Global Journal of Medical Research, 2019)
The geriatric population, atrophic maxilla is a common condition. 1. Severely resorbed maxilla is challenging for the installation of conventional osseointegrated implants. 2. To reduce the complications associated with bone grafting procedures and to simplify the rehabilitation of atrophic maxilla, zygomatic implants play an essential role. 3. With the use of zygomatic implants the wait for osseous graft maturation is eliminated saving the treatment time and money. 4. In this case report, nasal floor lift for anterior implants was performed with placement of bilateral zygomatic implants and conventional implants.